Stochastic approach to heterogeneity in short-time announcement effects on the Chilean stock market indexes within 2016-2019 - Stehlík, Milan; Leal, Danilo; Kiseľák, Jozef; Leers, Joshua; Střelec, Luboš; Fuders, Felix (Taylor and Francis, 2024)
We aim to examine stock market returns before and after key events in the U.S. Sino trades between 2016 and 2019. The study tracks Cumulative Abnormal Returns (CAR) of the Índice de Precio Selectivo de Acciones (IPSA or S&P/CLX IPSA is a Chilean stock market index) for 26 important events throughout this time period. By testing for both directions and significance of market reaction to said events this study aims to clarify if these events and policy announcements were sufficient to influence local equity markets, and in which direction. A simple analysis of CAR showed 16 negative reactions and 10 Positive reactions. An estimated 13 billion USD in market capitalization was lost as a result. Of the 26 events studied 18 were found to produce statistically significant reactions and 8 did not. The IPSA’s reaction to the significant events was mixed with 11 negative reactions and 7 positive reactions. We also checked for the normality of the distribution by robust normality tests and expected returns possess significant asymmetry and above-normal kurtosis. As such on aggregate it can be concluded that Chilean capital markets reacted negatively to the U.S. Sino trade war. We model IPSA in the period 2016–2022, where we can observe qualitative differences before and after 2019. To the best knowledge of the authors, the model of IPSA in this article is the first attempt in this direction.
Keywords: Chilean capital markets; Cumulative abnormal returns; Event studies; Primary 60H10; Secondary 60H30; Stochastic model of interest rate; Stock market data